THE DINAMICS OF MAJOR-POWER RELATION AND ITS INFLUENCES TOWARD ASIA-PACIFIC REGIONAL ORDER IN CONTEMPORARY ERA - Iriawan, Sony (Jurnal Pertahanan dan Bela Negara, 2018)
Asia-Pacific as the "pivot" of the 21st century area, related to the various issues that became the main agenda when discussing the development of international politics today. The dynamics of major-power relations as the complexity of the USA-China relations has effect significantly to the regional order in Asia Pacific. The urgency of reshaping the regional order in Asia Pacific is when China as an emerging power presenting a threat towards US hegemony existence in the region. The dynamics of major-power relations have indirectly created perceptions of the strengthening of China's influence in the regional level, which leads to the centralistic weakening of US leadership in Asia-Pacific. Simultaneously, the creation of peace and the stability of regional security also demands the re-establishment of an Asia-Pacific regional order that can accommodate the possibility of a truly transitional US power over China. Keyword: major-power relation, world order, Asia-Pacific, United States of America, the rise of China